Digital activism and cyberconflicts in Nigeria : Occupy Nigeria, Boko Haram and MEND - Olabode, Shola Abidemi (Digital activism and society., 2018)
This book offers fresh insights on digital activism and cyberconflicts through a comparison of sociopolitical and ethnoreligious movements in Nigeria. Occupy Nigeria, Boko Haram and The Movement for the Emancipation of the Niger Delta (MEND) highlight the digital and organizational aspects of conflict mobilization in contemporary Nigeria.